High-sensitivity C reactive protein and risk of cardiovascular disease in China-CVD study. Issue 2 (7th December 2018) - Dong, Ying; Wang, Xin; Zhang, Linfeng; Chen, Zuo; Zheng, Congyi; Wang, Jiali; Kang, Yuting; Shao, Lan; Tian, Ye; Wang, Zengwu
Abstract : Background: This study aimed to assess the association of high sensitivity C-reactive protein (hs-CRP) with cardiovascular disease (CVD) in middle-aged Chinese population. Methods: The baseline was collected 2009–2010, and follow-up was conducted in 2016–2017. Data of hs-CRP were from baseline examination and re-examination in 2016–2017 using transmission turbidimetry with a measurement range of 0–42 000. The primary outcome was CVD including coronary heart disease events and stroke events. Results: Among 8688 participants free from CVD (at baseline, mean age, 50.1 years, 3897 were males), there were 189 CVD events, occurred during a median follow-up of 6.34 years (54 685 person-years at risk). From the Kaplan-Meier curve, we found that there was a progressive increase in CVD event rates by hs-CRP tertiles (log-rank test, p<0.001). Baseline hs-CRP was linearly associated with CVD (p for trend=0.015) even after adjusting for known CVD risk factors. Furthermore, the net reclassification improvement when hs-CRP was added to a model based on traditional factors was 7.85% for CVD (p=0.003). In addition, the correlation between change of hs-CRP and CVD was conducted in a subgroup (n=4778). However, we did not find the correlation between hs-CRP change and CVD (correlation coefficient: −0.003, p=0.846). Conclusions: In the middle-aged Chinese population, hs-CRP was associated with increased risk of developing CVD. Although there was no correlation between hs-CRP change and CVD, the level of hs-CRP was higher at follow-up than baseline even among those with CVD. More attention should be given to those with higher level of hs-CRP for CVD prevention.